Evaluation of the IMF's Role in Poverty Reduction Strategy Papers and the Poverty Reduction and Growth Facility - Goldsbrough, David (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2004)
In 1999, the IMF and the World Bank adopted a new frame work for supporting economic reform in low-income member countries to achieve the objectives of poverty reduction and economic growth. The frame work consists of two key elements: country-authored Poverty Reduction Strategy Papers, drawing on broad-based consultations with key stake holder groups; and a vehicle for the provision of IMF concessional lending, the Poverty Reduction andGrowth Facility. This evaluation takes stock of progress to date and attempts to identify short comings that may require course corrections in the design and implementation of the initiative.